Peningkatan Kompetensi Guru PAUD melalui Pelatihan Disiplin Positif untuk Mendukung Pembentukan Karakter Anak - YAYU RAHAYU; Agus Kusnandar Kusnandar; Nenden Sri Rahayu Rahayu; Imas Suryati Suryati (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
This Community Service (PKM) activity aimed to enhance ECE teachers' understanding and skills in implementing positive discipline to support children's character formation, self-regulation, and independence. The program was conducted across five Islamic ECE institutions in Bekasi City, involving 25 participants comprising 15 teachers, 5 principals, and 5 supervisors. A participatory experiential learning approach was applied through four stages: need assessment, workshop, coaching, and evaluation. Data were collected using pre-test and post-test instruments based on revised Bloom's taxonomy indicators, structured observation rubrics, and teacher reflection worksheets. Results showed a significant increase in teachers' mean scores from 52.87 to 78.07 (+47.67%), alongside observable improvements in empathic communication, logical consequences application, and positive behavior reinforcement in the classroom. These findings indicate that participatory experiential learning training combined with direct coaching effectively enhances teachers' cognitive and practical competencies, contributing to a more humane learning environment that supports children's social-emotional development.